“ZARPAR”—Educational Program for Cognitive and Behavioral Development: Results of an Experiment to Evaluate Its Impact on Antisocial and Pro-Social Behavior - Santos, Gilda (International journal of offender therapy and comparative criminology, 2025)
Using an experimental design and a multi-measure and multi-informant approach, the current study sought to evaluate the impact of the early developmental prevention program “ZARPAR”—an intervention designed as a social and cognitive skills training program, that seeks to promote children’s behavioral adjustment. A sample of elementary school children (experimental group n = 37; control group n = 66), attending Portuguese schools, was assessed before and 6 months after the intervention on the program’s key-dimensions: behavioral problems, social skills, and executive functioning. Based on parent and teacher reports, the results largely suggested that the intervention had no effect or, for some dimensions, even the existence of negative outcomes. Possible reasons for these results are discussed. The current study highlights that, despite the overwhelmingly positive message about developmental prevention programs, not all interventions work, thus reinforcing the need for rigorous evaluations, in order to enhance the success of future interventions.